The Rising Resilience of Emerging Market and Developing Economies - Abiad, Abdul (IMF Working Papers; Working Paper ;, 2012)
Economic performance in many emerging market and developing economies (EMDEs) improved substantially over the past twenty years. The past decade was particularly good-for the first time EMDEs spent more time in expansion and had smaller downturns thanadvanced economies. In this paper we document the history of EMDEs' resilience over the past sixty years, and investigate what factors have been associated with it. We find that their improved performance in recent years is accounted for by both good policies and a lowerincidence of external and domestic shocks-better policies account for about three-fifths of their improved resilience, while less frequent shocks account for the remainder.